Penggunaan Tanah di Kawasan Resapan Air Untuk Pemukiman Sesuai Asas Berkelanjutan - Alifika El Ul, Khaidara; Mukharom, Mukharom; Aryaputra, Muhammad Iftar (Jurnal Ilmu Hukum, Humaniora dan Politik, 2024)
The aim of this research is to determine and analyze the criteria for balanced land use in water catchment areas and ideal higher education so that they remain in accordance with sustainable principles and the efforts of the Semarang City Government in controlling the spatial planning of Semarang City, especially water catchment areas. The research method used by the author is an empirical juridical approach with analytical descriptive specifications. The source and type of data used in this research uses primary data in the form of interviews. Data analysis uses qualitative and the results of the data analysis that have been collected are drawn to conclusions and presented deductively. The results of the research found that the balanced criteria for land use in the water catchment area in Sekaran Subdistrict, which is the center of higher education, is not in accordance with Article 118 paragraph (2) of the Semarang City RTRW PERDA because the community does not build absorption wells and does not take into account the water that seeps into the ground which is not in accordance with the concept of sustainable development. Settlements located in water catchment areas can achieve balanced criteria if they implement 3 pro-development, namely pro-economic, pro-social justice, and pro-sustainable environment. The Semarang City Government's efforts are to create regulations that every boarding house must have a boarding house management permit as regulated in the Semarang City Perwal for Boarding House Management, one of the conditions of which is the IMB. However, the public is still indifferent to these regulations due to the lack of firm action by the Semarang City Government in carrying out supervision and imposing sanctions. The conclusion of this research is that land use in Sekaran Village, Gunungpati District does not meet the balanced criteria, especially in terms of pro-sustainable environment. The efforts of the Semarang City Government have not been fully effective due to the lack of firm action by law enforcement officials regarding violations of the law.